BUSINESS PLAN : BENE - Yurike Tandiara (CALYPTRA, 2014)
Scientific work in the form of non - research business plan is a healthy drinks business, with juices/ smoothies products, mix of fresh fruits and vegetables. This business plan aims to evaluate the feasibility of Bene. And also as a frame and reference in realizing and developing Bene in terms of various aspects of business, such as marketing, operations, finance, human resources, strategy and business feasibility of Bene. This business plan was made due to see an opportunity is still wide open in urban areas, especially in Surabaya, where there is stronger purchasing power, increased education and better health facilities, will make people pay more attention to quality. But on the other hand, people living in unhealthy patterns, instant paced and modern culture, the amount of air pollution and smoking habits that cause various health problems. Financial analysis of Bene was concluded that with initial capital of Rp 409 295 660, this business gives NPV of Rp 1,984,272,598 and an IRR of 91.71 % , and 2.12 years for the DPP. Average value of NPV, the DPP, and the IRR shows a positive NPV, the DPP is less than 5 years, and an IRR greater than the cost of capital of 14.3 %. Thus, it can be concluded that this business is feasible set.